2009
DOI: 10.3113/fai-2009-0415
|View full text |Cite
|
Sign up to set email alerts
|

Intermetatarsal Angular Change Following Fusion of the First Metatarsophalangeal Joint

Abstract: Both the intermetatarsal angle and position of the tibial sesamoid reliably improved following arthrodesis of the first MTP joint, negating the need for a separate osteotomy of the first metatarsal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 11 publications
(12 reference statements)
2
17
0
Order By: Relevance
“…We found that there was a mean correction of 6.0 degrees, comparing the preoperative and immediate postoperative radiographs, and 5.8 degrees, comparing the preoperative and late postoperative radiographs. Our data corroborate the findings of other authors, in which the mean corrections were 5.7 (13) , 4 (14) , 4.4 (15) , 4.4 (12) and 8.2 (11) . It is believed that the alignment of the first radius restores the anatomical relationships and function of the intrinsic and extrinsic musculature and plantar aponeurosis.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We found that there was a mean correction of 6.0 degrees, comparing the preoperative and immediate postoperative radiographs, and 5.8 degrees, comparing the preoperative and late postoperative radiographs. Our data corroborate the findings of other authors, in which the mean corrections were 5.7 (13) , 4 (14) , 4.4 (15) , 4.4 (12) and 8.2 (11) . It is believed that the alignment of the first radius restores the anatomical relationships and function of the intrinsic and extrinsic musculature and plantar aponeurosis.…”
Section: Discussionsupporting
confidence: 93%
“…Since arthrodesis does not directly address varus deformity of the first metatarsal, there are doubts in relation to patients with an increased intermetatarsal angle regarding whether the varus deformity can be corrected by means of arthrodesis of the first metatarsophalangeal joint alone, or whether osteotomy at the base of the first metatarsal is necessary 11 , 12 . Many techniques for arthrodesis of the first metatarsophalangeal joint have been described in the literature, but few authors have investigated the change in intermetatarsal angle after arthrodesis 11 , 13 , 14 , 15 , 16 .…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have already correlated arthrodesis of the MTP of the hallux with correction of the intermetatarsal angle I-II 20 , 21 , 22 and have observed a mean correction of 3° to 8° in this angle. This demonstrates that arthrodesis of the MTP joint of the hallux improves the varus nature of the first ray and makes it unnecessary to associate basal osteotomy in order to correct the intermetatarsal angle.…”
Section: Discussionmentioning
confidence: 88%
“…12 These authors emphasized that previous studies evaluating 1-2 IMA correction in patients undergoing first MTP fusion included bunions of varying severity. 5,10,12…”
Section: Discussionmentioning
confidence: 99%